2021
DOI: 10.1111/evo.14157
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of coordinated plasticity across functional units in a Lake Malawi cichlid mapping population

Abstract: Adaptive radiations are often stereotypical, as populations repeatedly specialize along conserved environmental axes. Phenotypic plasticity may be similarly stereotypical, as individuals respond to environmental cues. These parallel patterns of variation, which are often consistent across traits, have led researchers to propose that plasticity can facilitate predictable patterns of evolution along environmental gradients. This "flexible stem" model of evolution raises questions about the genetic nature of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
(113 reference statements)
3
3
0
Order By: Relevance
“…A number of general themes emerge from these data. First, they provide clear support for the hypothesis that foraging environment influences the genotype-phenotype map for craniofacial skeletal traits (Parsons et al, 2016;Navon et al, 2021;Zogbaum et al, 2021). More specifically, our data suggest that pelagic foraging "drives" species-and environment-specific DE.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A number of general themes emerge from these data. First, they provide clear support for the hypothesis that foraging environment influences the genotype-phenotype map for craniofacial skeletal traits (Parsons et al, 2016;Navon et al, 2021;Zogbaum et al, 2021). More specifically, our data suggest that pelagic foraging "drives" species-and environment-specific DE.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, to address the question of genetic and epigenetic control of plasticity in the cichlid feeding apparatus, we utilize two complementary methods of assessing transcriptional output: RNA-seq to analyze gene expression, and ATAC-seq to assess chromatin accessibility. We focused on an important functional complex -i.e., the interopercle-retroarticular (IOP-RA) complex -which (1) is part of the opercle 4-bar linkage chain, (2) helps to drive lower jaw depression, (3) is comprised of hard and soft tissues, (4) varies among Malawi cichlids in a manner that predicts foraging mode/habitat, and (5) has been shown to be plastic in previous research (Figure 1; Hu and Albertson 2014;Navon et al 2021). Our goals are to identify genes that are both differentially expressed (DE) and differentially accessible (DA) between species and environments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of general themes emerge from these data. First, they provide further support for the hypothesis that foraging environment influences the genotype-phenotype map for craniofacial skeletal traits (Navon et al, 2021;Parsons et al, 2016;Zogbaum et al, 2021). More specifically, our data suggest that pelagic foraging is an especially potent driver of species-and environment-specific differential gene expression.…”
Section: Con Clus Ionssupporting
confidence: 72%
“…We utilize two complementary methods of assessing transcriptional output: RNA-seq to analyse gene expression and ATAC-seq to assess chromatin accessibility. We focus on an important functional complex-that is, the interopercleretroarticular (IOP-RA) linkage-which (1) is part of the opercle 4bar system, (2) helps to drive lower jaw depression, (3) is comprised of hard and soft tissues, (4) varies among Malawi cichlids in a manner that predicts foraging mode/habitat, and (5) has been shown to be plastic in previous research (Figure 1; Hu & Albertson, 2014, 2017Navon et al, 2021). Environmental input is explicitly incorporated into our experimental design, as we force animals to collect prey in a manner that mimics alternate benthic-pelagic modes of feeding.…”
mentioning
confidence: 99%
“…The two groups developed into adults with distinctly different head-jaw structures that were tailored to forage for the available food most effectively. Navon et al reported on a similar experiment that confirmed the Parsons et al results (Navon et al 2021). The investigators also demonstrated diet-induced adaptive changes to body shape and fin-ray number.…”
Section: Cichlidssupporting
confidence: 52%